TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PERDA KOTA SAMARINDA NOMOR 12 TAHUN 2013 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA DALAM WILAYAH KOTA SAMARINDA - Surya Hidayat Limbong (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTIndonesia is a country with abundant natural wealth, which are of mineral. Minerals mine in Indonesia is of mineral excellent and desired by other countries and is used for the people's welfare. Therefore, in order to empower the wealth of mine made the policies in regulating mining activities. Samarinda city that has made the natural wealth in mining Regulation Number 12th at year 2013 on Mineral and coal. This study aims to determine how the implementation of this regulation in the field. Is this regulation is able to answer the needs of mining in samarinda, given the conditions of Samarinda which has now begun damaged surrounded by mining activity. The results showed (1) of this regulation has many defects in its formulation, ranging from using uu that are not used again until many chapters in this regulation as opposed to uu rules above, (2) This regulation does not set the auction process in the process WIUP manufacture. (3) Certificate of Original (SKAB in indonesian) also published in this regulation, whereas SKAB is no longer allowed to be applied based on the Circular Letter of the Directorate General of Mineral and Coal, Ministry of Energy and Mineral Resources Number 02 E / 30 / DJB / 2012. In response to the above, then by reducing the Mining Permit and crack down on violators could be a stepping stone in order to be saved from Samarinda City Environmental Damage which is increasingly severe. In addition to planning a Mining Rule Government should examine in depth so that the Regulation is derived can be executed and implemented in line with expectations without damaging the environment.